PulseNet Latin America and the Caribbean Network: Present and Future - Chinen, Isabel (2019)
Fil: Chinen, Isabel. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio Fisiopatogenia; Argentina.